Students’ Perception on Vocabulary Development Using Video Animation Animaker during Online Learning Covid-19 Pandemic - Rochmatul Lathifah; Ribeh Najib Muhammad (Universitas Muhammadiyah Gresik, 2022)
Video animation animaker is one of the media currently used by various people, one of which is used in online learning. Video animation animaker is also one of the learning media that has been implemented by several educational circles before and after covid-19 pandemic. This study is aimed to investigate the efficiency of doing online learning using video animation animaker towards vocabulary development. The objective of this study is to figure out whether the use of video animation animaker improve students’ vocabulary during online learning pandemic covid-19 in SMPN 31 Gresik. The participant of this research was students at seventh grade with total 4 class of SMPN 31 Gresik in academic year 2020/2021. The total of the students was 100 students. The analysis in this study uses qualitative methods, with the data obtained by questionnaires and interviews. There are 20 items of questionnaire given to students using google form and 5 questions for interviews.